Selective targeting of cancer signaling pathways with nanomedicines: challenges and progress - Abul Barkat, Harshita; Sachi Das, Sabya; Abul Barkat, Md; Beg, Sarwar; Ab. Hadi, Hazrina (Future Medicine, 2020)
Cancer is one of the leading causes of death worldwide. Regardless of advances in understanding the molecular mechanics of cancer, its treatment is still lacking and the death rates for many forms of the disease remain the same as six decades ago. Although a variety of therapeutic agents and strategies have been reported, these therapies often failed to provide efficient therapy to patients as a consequence of the inability to deliver right and adequate chemotherapeutic agents to the right place. However, the situation has started to revolutionize substantially with the advent of novel ‘targeted’ nanocarrier-based cancer therapies. Such therapies hold great potential in cancer management as they are biocompatible, tailored to specific needs, tolerated and deliver enough drugs at the targeted site. Their use also enhances the delivery of chemotherapeutics by improving biodistribution, lowering toxicity, inhibiting degrada- tion and increasing cellular uptake. However, in some instances, nonselective targeting is not enough and the inclusion of a ligand moiety is required to achieve tumor targeting and enhanced drug accumulation at the tumor site. This contemporary review outlines the targeting potential of nanocarriers, highlighting the essentiality of nanoparticles, tumor-associated molecular signaling pathways, and various biological and pathophysiological barriers.